Effect of Different Feeding on The Growth Rate of Maggots (Hermetia illucens) - Nurjayanti, Dwi; Jayanthi, Sri; Syafira, Yuni; Yanti Br Dalimunte, Elvina; Nur, Ulfatun; Azhari Tanjung, Rizkan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Population growth and high consumption patterns have led to increased waste production. This encourages people to look for effective and economically valuable solutions. One potential action that can be taken is to convert organic waste into practical utilization as food for maggot (H. illucens). Maggot (H. illucens) is one of the decomposer organisms that has a fairly high nutritional content. The objective of this study was to evaluate the impact of various feed ingredients, including vegetable waste, rice husk and bran, on the growth rate of larvae (H. illucens). The study was conducted from October to November 2024 in Meurandeh, Langsa Lama, using experimental methodology with a Rancangan Acak Lengkap (RAL) with 6 treatments and 4 repetitions for 21 days. P1: 100% bran, P2: 100% vegetable waste, P3: 100% rice, P4: combination (50% bran + 50% vegetable waste), P5: combination (50% bran + 50% rice), P6: combination (50% bran + 25% vegetable waste + 25% rice. The results showed that treatment A produced the highest absolute biomass of maggots (H. illucens), with an average of 204.25 grams, while treatment B recorded the lowest absolute biomass of maggots (H. illucens), with an average of 157.25 grams. And the highest organic waste composition for maggot length growth (H. illucens) The average length recorded in treatment E was 3.88 cm, while treatment F showed the shortest average length. The Anova results show that different feeding has no significant effect (P>1.112) total weight of biomass maggot (H. illucens), this shows that one of the elements that influence maggot growth is the quality of feed that is rich in protein and normal water content so that it can allow maggot to receive nutrients optimally.